Innovative Religious Science Education: Incorporating Virtual Reality to Teach Complex Theological Concepts - Siti Mahmudah; Muhammadong Muhammadong (Journal of Social Science Utilizing Technology, 2024)
Background. Religious science education often faces challenges in conveying complex theological concepts to students in a way that is engaging and easily understood. Traditional teaching methods may struggle to capture abstract or difficult ideas, resulting in a disconnect between theoretical knowledge and practical understanding. Recent advancements in technology, particularly virtual reality (VR), offer innovative solutions to enhance learning experiences in this field. Virtual reality has the potential to immerse students in interactive, three-dimensional environments, allowing them to explore theological ideas more deeply. Purpose. This study aims to explore the effectiveness of incorporating virtual reality into religious science education to teach complex theological concepts. Method. A mixed-methods approach was used, combining qualitative interviews with students and educators, along with a quantitative assessment of student performance before and after VR integration. The study was conducted at three religious institutions where VR modules were introduced in the curriculum to teach topics such as creation, eschatology, and religious symbolism. Results. Results indicate that students demonstrated a significant improvement in understanding and retaining complex theological concepts when virtual reality was incorporated into the learning process. The immersive nature of VR allowed students to engage with the material more deeply, leading to greater comprehension and participation. Additionally, educators reported that VR enhanced the overall classroom experience by making abstract concepts more accessible.. Conclusion. In conclusion, virtual reality presents a promising tool for religious science education, providing an innovative approach to teaching complex theological ideas. Future research should explore long-term impacts and scalability of VR in religious education.